ANALYSIS OF HEALTH SERVICE RETRIBUTION RATES FOR PRIMARY HEALTHCARE CENTERS IN CIMAHI CITY - Budiman Budiman; Ayu Laili Rahmiyati; Lina Safarina (Universitas Airlangga, 2021)
ABSTRACTRetribution Tariff of Public Health Center (Puskesmas) in Cimahi City is regulated according to Regulation of Retribution Tariff according to Regulation No. 8 Year 2011. Based on the tariff value from 2011 until now still valid with same tariff. Based on the above, it is necessary to evaluate the tariff compared with the increase of the price of health equipment and the operational cost of other puskesmas supporting the puskesmas service, which increases annually.. The purpose of this research is to analyze the tariff of puskesmas. This research method is qualitative descriptive research. Result of research indicate that tariff of puskesmas service there are several alternatives along with the increase of tools, drugs and raw materials, this becomes the base of tariff policy consideration, with consideration of price increase of puskesmas tariff or addition of health budget subsidy in Cimahi City. Conclusion: Based on the unit cost of indirect cost calculation tariff of public health service Rp 26,973, -. Based on the total cost (total cost) of public health services Rp 62,529, - Based on the comparison of other city tariffs from the mayor regulation of 2011-2012 is Rp 2000, - to Rp 4000, -. Based on the proposals from the Disccusion Focus Group (FGD), several public health centers in Cimahi City, on average, were Rp 8,500. Based on the academic proposal, the average inflation rate (Rp 11,000), ability to pay (Rp 9,475, -) cost (Rp 11,507), generic drug cost (Rp 6,556, -), average proposals of puskesmas (Rp 8,500, -), namely: Rp 11,567, - rounded Rp 11.000, -. Keywords: Analysis, Retribution Tariff of Puskesmas